Pengembangan Ekspor Produk Kelautan Indonesia ke Eropa - Achmad Fahrudin (Buletin Ekonomi Perikanan, 2003)
The opportunity to Increase the export volume of Southeast and East Asia marine product is far more significant In the future (until more than 12.50%). This Is related to the European state agreement to decrease fish catching. around European area. This opportunity is a challenge for Indonesian marine products to improve their perfonnance. Indonesia could give a solution for several constraints, by increasing the quality and developing the transport services. The development of exploitation and post harvest, biotechnology industry and Increasing Information flow are several steps to improve marine product development In Indonesia to compete with other countries.